2010
DOI: 10.1007/s12600-010-0083-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis of Eucalyptus plants on Podisus nigrispinus

Abstract: The predator Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) has been used as a natural enemy to control herbivorous insects in eucalyptus plantations. However, because of the short coevolutionary history of the predator with this imported plant species, the defensive compounds of eucalyptus may have a negative effect on the predator. Therefore, the survival and development of P. nigrispinus were studied on eucalyptus (Eucalyptus urophylla; exotic host plant) and guava (Psidium guajava; native host pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…Isso pode ser verificado em diversos trabalhos em laboratório (Holtz et al, 2010;Lemos et al, 2001) ou no campo (Oliveira et al, 2002b). Ambos os períodos de pré e pós-oviposição mais curtos permitem maior alocação de energia no período de oviposição (De Bortoli et al, 2011), que pode ser mais longo, como observado nas dietas com farelo de trigo e ração de galinha poedeira peletizada.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Isso pode ser verificado em diversos trabalhos em laboratório (Holtz et al, 2010;Lemos et al, 2001) ou no campo (Oliveira et al, 2002b). Ambos os períodos de pré e pós-oviposição mais curtos permitem maior alocação de energia no período de oviposição (De Bortoli et al, 2011), que pode ser mais longo, como observado nas dietas com farelo de trigo e ração de galinha poedeira peletizada.…”
Section: Discussionunclassified
“…Além da criação de P. nigrispinus, larvas, pupas e adultos de T. molitor podem ser utilizados na criação de outros predadores (Grundy et al, 2000;Zanuncio et al, 2004), parasitoides (Zanuncio et al, 2008;Andrade et al, 2010), pássaros (Martinson;Flaspohler, 2003), morcegos (Mccartney et al, 2007), aranhas (Japyassú;Jotta, 2005), peixes (Ng et al, 2001) e lagartos (Font; Molina-Borja, 2004) e na degradação de resíduos de criatórios de aves (Fischer et al, 2004).…”
Section: Palavras-chaveunclassified
“…Herbivory-induced plant volatiles, such as terpenes, are indirect defenses, which attract the natural enemies of herbivores. The resistance noted in the varieties belonging to the African rice species O. glaberrima could result from the coevolution between that species and the microorganisms in an environment marked by the presence of several biotic and abiotic stresses (Holtz et al, 2010). Research directed towards the isolation of endophytes in the plant tissues of the rice varieties studied would reveal a difference in diversity between susceptible and resistant individuals (Zakaria, Yaakop, Salleh, & Zakaria, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…After this study, Brazilian researchers focused on studies regarding the response of the predator Asopinae to the plant defense induced by the herbivore (HOLTZ et al, 2008), and in studies on antibiosis showed that the predator is not fully adapted to the exotic host plant, as demonstrated in its biological and reproductive characteristics (HOLTZ et al, 2010).…”
Section: Scientific Contributions In the Field Investigating Resistanmentioning
confidence: 99%